2018
DOI: 10.1016/j.apsusc.2018.08.156
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial bonding mechanisms between aluminum and titanium during cold gas spraying followed by friction-stir modification

Abstract: This paper closely evaluates the interfacial bonding mechanism between titanium particles deposited on an aluminum alloy substrate by cold gas spraying followed by friction-stir processing (FSP). After cold spraying and FSP modification, the produced Al/Ti interface was studied using focus ion beam-transmission electron microscopy (FIB-TEM) analysis and auger electron spectroscopy. Formation of a well-bonded titanium aluminide reaction layer was observed at the interface with a thickness in the range of 10-20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Owing to these advantages, many attempts have been made to modify CS deposits, such as Ti [160], CuZn alloy [161], 7075Al alloy [162], NiTi alloy, and MMCs [149,150,163,164]. A hybrid AM technique combined with CS and FSP post-processing has been developed for component manufacturing and repairing (Fig.…”
Section: Post Friction Stir Processing Treatmentmentioning
confidence: 99%
“…Owing to these advantages, many attempts have been made to modify CS deposits, such as Ti [160], CuZn alloy [161], 7075Al alloy [162], NiTi alloy, and MMCs [149,150,163,164]. A hybrid AM technique combined with CS and FSP post-processing has been developed for component manufacturing and repairing (Fig.…”
Section: Post Friction Stir Processing Treatmentmentioning
confidence: 99%
“…The necessity of removing the native oxide layer on particle-substrate surfaces for the creation of metallurgical bonding is widely acknowledged in the CS literature but the details of the in situ oxide layer removal process is still a point of contention. Numerous studies have indicated that adiabatic shear instability is the main mechanism responsible for the oxide layer breakup and cleaning away (removal) (Ref 18,19,22,23,(31)(32)(33)(34), while some have elaborated that metallurgical bonding in CS is not related to the occurrence of adiabatic shear instability (Ref 24,35). In addition, partial melting in the contact region has also been deemed responsible for the localized oxide layer removal and chemical bonding upon solidification (Ref 36,37).…”
Section: Introductionmentioning
confidence: 99%
“…However, the particles added in this way are easy to slip and splash during the FSP process; hence, there is an inhomogeneous distribution of the strengthening phases and a loss of material. Based on this method, pre-fabricated surface composites can be fabricated by cold spraying [44,45] or laser melting [46] with further processing of the coating via FSP. This can improve the microstructure and the distribution of the reinforced particles to obtain surface composites with better properties.…”
Section: Methods Of Adding Reinforced Particlesmentioning
confidence: 99%